The teaching of aircraft design - Newell, A. F.; Howe, D. (College of Aeronautics, 1964)
Aircraft Design has been taught at the College of Aeronautics since 1946. The course is at postgraduate level and is of two years duration. In the first year the students are given three exercises in component design which aim to teach a logical approach and the fundamentals of the subject. During the second year each student works as a member of a team engaged in the design of a complete aircraft, which is chosen to be of a type currently being investigated by industry. The project aircraft invariably incorporates experimental features and the design work is therefore of the nature of research.